(untitled) (Jurnal Riset Manajemen Akuntansi Indonesia, 2024)
The aim of this research is to find out why human resource development through improving educational facilities at the Magelang Military Academy is still not optimal, to find out the strategy for developing human resources through improving educational facilities at the Magelang Military Academy. The results of the research show that the cause of human resource development through improving educational facilities at the Magelang Military Academy is still not optimal because the development of science and technology demands the development of human resources and educational facilities, educational facilities are limited due to budget constraints, maintenance of educational facilities needs to be improved because they are often used so that damage can occur. minimized, lack of creativity of human resources (Gadik) in utilizing available educational facilities as learning media. The strategy for developing human resources through improving educational facilities at Akmil Magelang is the SO Strategy carried out by increasing coordination and guidance by Akmil Magelang, increasing cooperation with other units and increasing cooperation with the Government. upgrading or upgrading, the ST Strategy is carried out by increasing understanding of the main tasks and functions and increasing socialization to the community and the WT Strategy is carried out by improving educational facilities and improving maintenance of educational facilities.